Amorphous metal metaphosphate composite material and preparation method and application thereof

By preparing amorphous metal metaphosphate composite materials, the problem of poor electrocatalytic activity of zinc-air battery catalysts is solved, and the efficient catalytic performance and stability of zinc-air battery are achieved, which is suitable for market promotion.

CN114420954BActive Publication Date: 2025-02-11WUHAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111653870.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-30
Publication Date
2025-02-11
Estimated Expiration
2041-12-30

AI Technical Summary

Technical Problem

The catalytic kinetics of the existing zinc-air battery catalysts are slow and limiting the overall efficiency and energy/power output of zinc-air battery.

Method used

Using an amorphous metal metaphosphate composite material, the metal chloride and carbon material are dissolved in the carbon nitride dispersion, phytic acid is added, and lyophilized and calcined in an argon atmosphere are formed to form an amorphous structure with excellent catalytic properties.

Benefits of technology

It improves the intrinsic activity of the catalyst and the electrocatalytic performance of oxygen reduction, significantly improves the overall efficiency and energy/power output of zinc-air batteries, and has simple process and mild conditions, which is suitable for market promotion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114420954B_ABST
    Figure CN114420954B_ABST
Patent Text Reader

Abstract

The present invention provides an amorphous metal metaphosphate composite material and a preparation method and application thereof, wherein the preparation method comprises the steps of: dissolving a metal chloride and a carbon material in a carbon nitride dispersion or monodisperse polystyrene microspheres, adding phytic acid, and stirring to obtain a mixed solution; subjecting the mixed solution to a freeze-drying treatment to obtain a precursor; placing the precursor in a porcelain boat and placing it in a tubular furnace, and calcining it under an argon atmosphere to obtain an amorphous metal metaphosphate composite material. The present invention interrupts the spatial ordering of atoms through coupling at the interface between metal ions and carbon materials to form an amorphous structure, so that the metal ions as active centers are evenly dispersed and more exposed to the surface, thereby improving the intrinsic activity of the catalyst, showing excellent oxygen reduction electrocatalytic performance, and using the composite material to assemble a zinc-air battery, the maximum discharge power reaches 112.7mW / cm 2 , comparable to the precious metal Pt / C catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanomaterials and electrochemical catalysis, and in particular to an amorphous metal metaphosphate composite material and a preparation method and application thereof. Background Art

[0002] With the continuous growth of the world's population and the continuous advancement of industrialization, energy supply, especially the use of fossil fuels, has caused widespread concern about climate change, environmental pollution and other issues. The development of sustainable renewable energy, such as clean energy such as solar energy, wind energy and hydropower, is crucial, but its inherent randomness, intermittency and other shortcomings seriously restrict its widespread application. Therefore, timely energy storage and conversion has become a key link that needs to be solved in solar energy, wind energy and other technologies at this stage. Electrochemical energy storage and conversion technology based on water-hydrogen-oxygen, such as alkaline fuel cells, proton exchange membrane fuel cells, metal-air batteries, etc., has become one of the important research hotspots.

[0003] Zinc-air batteries are one of the most attractive metal-air batteries due to their non-flammability, high safety, high energy density, stable discharge voltage and long cycle life. However, the overall efficiency and energy / power output of zinc-air batteries are greatly limited due to the sluggish catalytic kinetics of oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). So far, platinum group metal-based materials with high catalytic activity, such as platinum, palladium and their alloys, are generally considered to be the most advanced ORR catalysts. However, the high price, small reserves, easy poisoning and poor cycle stability of precious metal elements have greatly hindered their industrial application. Therefore, there is an urgent need to develop efficient, low-cost and stable non-precious metal electrocatalysts.

[0004] Among the many non-precious metal catalysts, transition metal metaphosphates / phosphates have a relatively stable structural composition and can stabilize the intermediate state of transition metal ions, thus arousing widespread research interest. In addition, theoretical studies and experiments have also shown that phosphoric acid / metaphosphate groups can promote the proton transfer process, which is of great significance for catalytic reactions. However, the ORR electrocatalytic activity of transition metal phosphates still needs to be further improved. Summary of the invention

[0005] In view of this, the present invention provides an amorphous metal metaphosphate composite material and a preparation method thereof to solve the problem of poor electrocatalytic activity of existing zinc-air battery catalysts.

[0006] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0007] A method for preparing an amorphous metal metaphosphate composite material comprises the following steps:

[0008] S1, dissolving metal chloride and carbon material in carbon nitride dispersion, adding phytic acid, and stirring to obtain a mixed solution;

[0009] S2, freeze-drying the mixed solution to obtain a precursor;

[0010] S5. Put the precursor into a porcelain boat and place it in a tube furnace, and calcine it under an argon atmosphere to obtain an amorphous metal metaphosphate composite material.

[0011] Optionally, in step S1, the metal chloride comprises MnCl 2 、FeCl 3 、CoCl 2 、NiCl 2 、ZnCl 2 and CuCl 2 One of them.

[0012] Optionally, in step S1, the carbon material includes one of carbon nanotubes, graphene oxide, carbon nitride and three-dimensional carbon spheres.

[0013] Optionally, in step S1, when the metal chloride and the carbon material are dissolved in the carbon nitride dispersion, the mass volume ratio of the metal chloride, the carbon material, the carbon nitride and the phytic acid is in the range of 50 mg:50 mg:50 mg:0.5 mL to 300 mg:300 mg:300 mg:5 mL.

[0014] Optionally, in step S2, the freeze-drying conditions include: the freezing temperature is in the range of -35°C to -45°C, and the freezing time is in the range of 48h to 96h.

[0015] Optionally, in step S3, the calcination conditions of the precursor include a calcination temperature in the range of 600°C to 900°C, a heating rate of 2°C min -1 To 10℃min -1 The calcination time is in the range of 1.5h to 2.5h.

[0016] Optionally, the preparation method of the carbon nitride dispersion includes: calcining urea in a muffle furnace to obtain carbon nitride powder, and ultrasonically dispersing the carbon nitride powder in deionized water to form the carbon nitride dispersion.

[0017] Optionally, the calcination conditions of the urea include a calcination temperature in the range of 400°C to 600°C, a heating rate of 2°C min -1 To 10℃min -1 The calcination time is in the range of 2h to 4h.

[0018] The second object of the present invention is to provide an amorphous metal metaphosphate composite material, which is prepared by the above-mentioned preparation method of the amorphous metal metaphosphate composite material.

[0019] The third object of the present invention is to provide an application of the amorphous metal metaphosphate composite material as described above in the field of zinc-air batteries.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) The present invention interrupts the spatial ordering of atoms through coupling at the interface between metal ions and carbon materials to form an amorphous structure, so that the metal ions as active centers are evenly dispersed and more exposed to the surface, thereby improving the intrinsic activity of the catalyst and showing excellent oxygen reduction electrocatalytic performance.

[0022] (2) The preparation process of the present invention is simple, the conditions are mild, and the equipment requirements are low. Based on its amorphous structure, a controllable freeze-drying method and subsequent argon atmosphere calcination are adopted. By changing factors such as the type of metal, the type of carbon material, and the proportion of phytic acid, a series of amorphous metal metaphosphate composite materials are prepared. The composite materials have certain universality and are conducive to market promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 The amorphous Mn(PO 3 ) 2 -C / CNTs / C 3 N 4 XRD patterns of composite materials;

[0025] Figure 2 The amorphous Mn(PO 3 ) 2 -C / CNTs / C 3 N 4 SEM images of the composite materials;

[0026] Figure 3 The amorphous Mn(PO 3 ) 2 -C / CNTs / C 3 N 4 TEM images of the composite materials;

[0027] Figure 4 The amorphous Mn(PO 3 ) 2 -C / CNTs / C 3 N 4 Linear scanning voltammetry curve of the composite material at 0.1mol / LKOH and 5mV / s scan rate, ring-disk linear scanning voltammetry curve, SCN - Linear sweep voltammetry curve of ion poisoning test, methanol tolerance and stability test graph;

[0028] Figure 5 The amorphous Mn(PO 3 ) 2 -C / CNTs / C 3 N 4 Composite material zinc-air battery performance characterization diagram: including zinc-air battery schematic diagram, open circuit voltage stability diagram, LED light display diagram, discharge curve and power curve diagram, rate performance diagram, discharge specific capacity diagram, and discharge stability test diagram. DETAILED DESCRIPTION

[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0030] It should be noted that in the description of the embodiments of the present application, the description of the term "some specific embodiments" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same implementation or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0031] The “in the range of” described in this embodiment includes both end values, such as “in the range of 1 to 100” includes both end values ​​of 1 and 100.

[0032] The present invention provides a method for preparing an amorphous metal metaphosphate composite material, comprising the following steps:

[0033] S1. Dissolve metal chloride and carbon material in carbon nitride (C 3 N 4 ) dispersion, adding phytic acid, and stirring to obtain a mixed solution;

[0034] S2, freeze-drying the mixed solution to obtain a precursor;

[0035] S5. Put the precursor into a porcelain boat and place it in a tube furnace, and calcine it under an argon atmosphere to obtain an amorphous metal metaphosphate composite material.

[0036] Among them, metal chlorides include manganese chloride (MnCl 2 ), ferric chloride (FeCl 3 ), cobalt chloride (CoCl 2 ), nickel chloride (NiCl 2 ), zinc chloride (ZnCl 2 ) and copper chloride (CuCl 2 ). Carbon materials include carbon nanotubes (CNTs), graphene oxide (GO), carbon nitride (C 3 N 4 ) and one of the three-dimensional carbon spheres (3D CS).

[0037] The present invention adopts a carbon material pre-adsorption strategy to regulate the chelation between metal ions and phytic acid molecules, prepares a precursor by freeze drying, and then obtains a transition metal metaphosphate complex catalyst (M(PO 3 ) 2 -C / CNTs / C 3 N 4 ,M=Mn,Fe,Co,Ni,Cu,Zn).

[0038] Thus, the spatial ordering of atoms is interrupted by coupling at the interface between metal ions and carbon materials, thereby forming an amorphous structure. Amorphous materials have long-range disorder and short-range order structures. It is the disordered arrangement and relatively loose structure of these atoms that lead to a large number of defects and coordination unsaturated structures, which can significantly improve the ORR catalytic activity; and the addition of carbon materials can accelerate the electron transfer rate and regulate the electronic structure of the compound. In addition, carbon materials also have a pre-adsorption effect on heavy metal ions, making their active sites more evenly distributed, improving the intrinsic activity of the material, and showing excellent oxygen reduction electrocatalytic performance.

[0039] Specifically, in step S1, when the metal chloride and the carbon material are dissolved in the carbon nitride dispersion, the mass volume ratio of the metal chloride, the carbon material, the carbon nitride and the phytic acid is in the range of 50 mg:50 mg:50 mg:0.5 mL to 300 mg:300 mg:300 mg:5 mL.

[0040] Furthermore, the stirring time is in the range of 0.5 h to 24 h.

[0041] It is understandable that carbon nitride C 3 N 4The dispersion can be commercially available or homemade. In the embodiment of the present invention, in order to improve the reaction stability, the preparation method of the carbon nitride dispersion includes: placing urea in a crucible and calcining it in a muffle furnace to obtain carbon nitride powder, and taking out the sample after drying and supercooling to obtain C 3 N 4 ; C 3 N 4 Ultrasonic dispersion in deionized water to form C 3 N 4 Dispersion.

[0042] The calcination conditions of urea include a calcination temperature in the range of 400°C to 600°C and a heating rate of 2°C min -1 To 10℃min -1 The calcination time is in the range of 2h to 4h.

[0043] Specifically, in step S2, the freeze-drying conditions include: a freezing temperature in the range of -35°C to -45°C, and a freezing time in the range of 48h to 96h. Preferably, the mixed solution is frozen at -40°C for 72h.

[0044] In step S3, the calcination conditions of the precursor include a calcination temperature in the range of 600°C to 900°C and a heating rate of 2°C min -1 To 10℃min -1 The calcination time is in the range of 1.5h to 2.5h.

[0045] The preparation process of the present invention is simple, the conditions are mild, and the equipment requirements are low. Based on its amorphous structure, a controllable freeze-drying method and subsequent argon atmosphere calcination are adopted. By changing factors such as the type of metal, the type of carbon material, and the proportion of phytic acid, a series of amorphous metal metaphosphate composite materials are prepared. The composite materials have certain universality and are conducive to market promotion.

[0046] Another embodiment of the present invention provides an amorphous metal metaphosphate composite material, which is prepared by the above-mentioned method for preparing the amorphous metal metaphosphate composite material.

[0047] Another embodiment of the present invention provides an application of the amorphous metal metaphosphate composite material as described above in the field of zinc-air batteries.

[0048] Compared with the crystal structure, the present invention constructs a carbon material to pre-absorb metal ions to form an amorphous metal metaphosphate composite material, which spatially interrupts the metal chelated phytic acid to form a large structure and can pre-absorb metal ions at the same time, restrict the coordination structure of phytic acid, make the metal ions as active centers dispersed evenly and expose more defective structures. When the composite material is applied to zinc-air batteries, it can show more excellent oxygen reduction performance.

[0049] On the basis of the above-mentioned embodiments, the present invention provides the following specific examples to further illustrate the present invention. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. The experimental methods without specifying specific conditions in the following examples are usually based on the conditions recommended by the manufacturer. Unless otherwise stated, percentages and parts are calculated by mass.

[0050] Example 1

[0051] This embodiment provides a method for preparing an amorphous metal metaphosphate composite material, comprising the following steps:

[0052] 1) 1mmol MnCl 2 , 100 mg CNTs dissolved in C 3 N 4 The dispersion (20 mL of deionized water) was stirred evenly, and then 5 mL of phytic acid solution was added and stirred continuously to obtain a mixed solution;

[0053] 2) The mixed solution was transferred to a 50 mL centrifuge tube, and freeze-dried at -40°C under vacuum conditions for 72 hours to obtain a precursor;

[0054] 3) Place the precursor in a porcelain boat and place it in a tube furnace, evacuate and fill with Ar atmosphere, 5℃min -1 The temperature was raised to 800℃ and kept at this temperature for 2h. After the tube furnace cooled down, the sample was taken out to obtain amorphous Mn(PO 3 ) 2 -C / CNTs / C 3 N 4 Composite materials.

[0055] The amorphous Mn(PO 3 ) 2 -C / CNTs / C 3 N 4 Taking composite materials as an example, the physical structure is determined by X-ray diffraction, infrared, Raman and transmission electron microscopy, and the following is obtained: Figure 1-3 The result graph is shown.

[0056] from Figure 1 It can be seen that the metal phosphate without carbon material has a crystalline structure, and the diffraction peaks at 20.4°, 27.5°, and 29.1° correspond to Mn(PO 3 ) 2 (JCPDS card number is 00-029-0892) (-112), (310) and (-222) planes. After adding carbon material, it becomes an amorphous structure. In its infrared spectrum, 3435cm -1 、1398cm -1、1099cm -1 、1045cm -1 、733cm -1 and 578cm -1 For hydroxyl radicals, PO 2 - Asymmetric stretching vibration, PO 2 - Symmetric stretching vibration, POP asymmetric stretching vibration, POP symmetric stretching vibration, and PO formed by hydrolysis of metaphosphate 4 3- The vibration peaks of the Raman spectrum and infrared spectrum of amorphous phosphate are consistent with those of the crystalline phase.

[0057] from Figure 2 , Figure 3 It can be seen that amorphous Mn(PO 3 ) 2 -C / CNTs / C 3 N 4 The composite material is granular in shape, with large particles consisting of carbon nanotubes (CNTs) and carbon nitride (C 3 N 4 ) nanosheets, and the diffraction rings in transmission are only the (002), (101) and (110) planes of graphite carbon.

[0058] This shows that the formation process of the present invention is to first pre-adsorb metal ions on the carbon material, restrict coordination, form a chelate, and then calcine under an argon atmosphere to obtain an amorphous manganese metaphosphate / CNTs / C 3 N 4 structure.

[0059] Amorphous Mn(PO) prepared in Example 1 3 ) 2 -C / CNTs / C 3 N 4 The oxygen reduction electrocatalytic performance of the composite material was measured by an electrochemical workstation (CHI760E). 3 ) 2 -C / CNTs / C 3 N 4 The composite material's rotating disk electrode, platinum black electrode and saturated calomel electrode were used as working electrode, counter electrode and reference electrode respectively, thus forming a three-electrode test system. Figure 4 shown.

[0060] from Figure 4 It can be seen that in 0.1 mol / L KOH solution, the linear sweep voltammetry test was carried out at a scan rate of 5 mV / s, and Mn(PO 3) 2 -C / CNTs / C 3 N 4 It has a relatively positive starting potential (0.92V) and half-wave potential (0.80V), and a limiting current of 6.4mA / cm 2 . Using SCN - The metal active site poisoning experiment showed that the metal site was the main active site. After adding methanol during the ORR process, Mn(PO 3 ) 2 -C / CNTs / C 3 N 4 It still maintains a stable current density, showing better methanol tolerance than Pt / C. At the same time, the stability test shows that the current retention rate is as high as 90.3% after 40 hours, which is significantly better than the precious metal Pt / C catalyst.

[0061] The amorphous Mn(PO 3 ) 2 -C / CNTs / C 3 N 4 The composite materials were assembled into zinc-air batteries and the battery performance was tested. Figure 5 The result graph is shown.

[0062] from Figure 5 It can be seen that the composite material assembled into a zinc-air battery shows a stable open circuit voltage and a maximum discharge power of 112.7 mW / cm 2 , which is better than the precious metal Pt / C catalyst (107.7mW / cm 2 ). In addition, the current rate performance is excellent and shows good reversibility. 2 At the discharge current density, its specific capacity is 830.2mAh / g Zn , the corresponding energy density is as high as 996.2Wh / kg. That is, amorphous Mn(PO 3 ) 2 -C / CNTs / C 3 N 4 The zinc-air battery assembled with the composite material showed excellent cycle stability. The zinc-air battery was used to light up an LED lamp to demonstrate that it can be used in practice.

[0063] Comparative Example 1

[0064] This comparative example provides a Mn(PO 3 ) 2 -C preparation method, comprising the following steps:

[0065] 1) 1mmol MnCl 2Dissolve in 20 mL of deionized water and stir evenly, then add 5 mL of phytic acid and continue stirring to obtain a mixed solution;

[0066] 2) The mixed solution was transferred to a 50 mL centrifuge tube, and freeze-dried at -40°C under vacuum conditions for 72 hours to obtain a precursor;

[0067] 3) Place the precursor in a porcelain boat and place it in a tube furnace, evacuate and fill with Ar atmosphere, 5℃min -1 Heat to 800℃, keep warm for 2h, take out the sample after the tube furnace cools down, and get the shaped Mn(PO 3 ) 2 -C material.

[0068] The Mn(PO 3 ) 2 -C material as an example, the linear sweep voltammetry test was carried out in 0.1mol / L KOH solution at a scan rate of 5mV / s. The results showed that Mn(PO 3 ) 2 -C has a relatively positive starting potential (0.87V) and half-wave potential (0.73V), and its limiting current is 5.1mA / cm 2 .

[0069] Example 2

[0070] This embodiment provides a method for preparing an amorphous metal metaphosphate composite material, which is different from Embodiment 1 in that:

[0071] In step 1), 1 mmol CoCl 2 100 mg CNTs were dissolved in CNTs that had been crushed by ultrasonic cell machine. 3 N 4 Stir evenly in aqueous solution (20 mL of deionized water);

[0072] The remaining steps and parameters were the same as those in Example 1 to obtain amorphous Co(PO 3 ) 2 -C / CNTs / C 3 N 4 Composite materials.

[0073] The amorphous Co(PO 3 ) 2 -C / CNTs / C 3 N 4 The composite material was tested by linear sweep voltammetry at a scan rate of 5 mV / s in a 0.1 mol / L KOH solution. The results showed that the amorphous Co(PO 3 ) 2 -C / CNTs / C3 N 4 It has a relatively positive starting potential (0.86V) and half-wave potential (0.78V), and its limiting current is 5.3mA / cm 2 .

[0074] Example 3

[0075] This embodiment provides a method for preparing an amorphous metal metaphosphate composite material, which is different from Embodiment 1 in that:

[0076] In step 1), 1 mmol MnCl 2 , 20 mg of graphene oxide (GO) was dissolved in 20 mL of deionized water and stirred evenly;

[0077] The remaining steps and parameters were the same as those in Example 1 to obtain amorphous Mn(PO 3 ) 2 -C / GO composites.

[0078] The amorphous Mn(PO 3 ) 2 -C / GO composites were tested by linear sweep voltammetry at a scan rate of 5 mV / s in 0.1 mol / L KOH solution. The results showed that Mn(PO 3 ) 2 -C / GO has a relatively positive onset potential (0.88 V) and half-wave potential (0.76 V), and its limiting current is 5.6 mA / cm 2 .

[0079] Comparative Example 2

[0080] This embodiment provides a method for preparing a metal metaphosphate composite material, which is different from Embodiment 1 in that:

[0081] In step 1), 1 mmol MnCl 2 , 50 mg of monodisperse polystyrene microspheres were dissolved in 20 mL of water and stirred evenly;

[0082] The remaining steps and parameters are the same as those in Example 1 to obtain Mn(PO 3 ) 2 -C / PS composite materials.

[0083] The Mn(PO 3 ) 2 -C / PS composites were tested by linear sweep voltammetry at a scan rate of 5 mV / s in 0.1 mol / L KOH solution. The results showed that Mn(PO 3 ) 2-C / PS has a relatively positive onset potential (0.87 V) and half-wave potential (0.73 V), and its limiting current is 5.1 mA / cm 2 .

[0084] In summary, by adding different carbon materials and metal salts, the amorphous structure can be maintained and the oxygen reduction performance is improved to a certain extent, indicating that the pre-adsorption of metal ions by carbon materials and the formation of amorphous metal metaphosphates are universal.

[0085] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. A method for preparing an amorphous metal metaphosphate composite material, characterized in that: The steps include: S1, dissolving metal chloride and carbon material in carbon nitride dispersion, adding phytic acid, and stirring to obtain a mixed solution; S2, freeze-drying the mixed solution to obtain a precursor; S3, placing the precursor into a porcelain boat and placing it in a tube furnace, and calcining it under an argon atmosphere to obtain an amorphous metal metaphosphate composite material; The carbon material includes one of carbon nanotubes, graphene oxide, carbon nitride and three-dimensional carbon spheres.

2. The preparation method according to claim 1, characterized in that: In step S1, the metal chloride includes one of MnCl2, FeCl3, CoCl2, NiCl2, ZnCl2 and CuCl2.

3. The preparation method according to claim 1, characterized in that: In step S1, when the metal chloride and the carbon material are dissolved in the carbon nitride dispersion, the mass volume ratio of the metal chloride, the carbon material, the carbon nitride and the phytic acid is in the range of 50 mg:50 mg:50 mg:0.5 mL to 300 mg:300 mg:300 mg:5 mL.

4. The preparation method according to any one of claims 1 to 3, characterized in that: In step S2, the freeze-drying conditions include: the freezing temperature is in the range of -35°C to -45°C, and the freezing time is in the range of 48h to 96h.

5. The preparation method according to claim 4, characterized in that: In step S3, the calcination conditions of the precursor include a calcination temperature in the range of 600°C to 900°C, a heating rate of 2°C min -1 To 10℃min -1 The calcination time is in the range of 0.5h to 2.5h.

6. The preparation method according to claim 1, characterized in that: The preparation method of the carbon nitride dispersion comprises: The urea is calcined in a muffle furnace to obtain carbon nitride powder, and the carbon nitride powder is ultrasonically dispersed in deionized water to form the carbon nitride dispersion.

7. The preparation method according to claim 6, characterized in that: The calcination conditions of the urea include a calcination temperature in the range of 400°C to 600°C and a heating rate of 2°C min -1 To 10℃min -1 The calcination time is in the range of 2h to 4h.

8. An amorphous metal metaphosphate composite material, characterized in that: The amorphous metal metaphosphate composite material is prepared by the preparation method of any one of claims 1 to 7.

9. Use of the amorphous metal metaphosphate composite material as claimed in claim 8 in the field of zinc-air batteries.

Citation Information

Patent Citations

  • FeP / C3N4 compound photocatalyst, and preparation method and application thereof

    CN107552083A

  • Preparation method and application of polypyrrole gel loaded copper and phosphorus atom composite material

    CN113381034A